Umbilical acupuncture combined with warm needle acupuncture for the treatment of residual numbness after lumbar disc herniation surgery: a protocol of a randomized controlled trial - Kaihua Song; Jiayue Cheng; Yuming Wang; Yang Shen; Chenxin Jiang; Shouhai Hong (Frontiers in Neurology)
BackgroundPostoperative residual numbness following lumbar disc herniation (LDH) surgery is a relatively common symptom. Existing drugs and physical therapies are not very effective. Acupuncture is effective for the treatment of LDH, but there are limited reports on its use for postoperative numbness. Based on clinical observations and literature review, we hypothesize that combining umbilical acupuncture (UA) with warm needle acupuncture(WA) may yield superior efficacy compared to electroacupuncture(EA) alone, enhancing immune function, promoting nerve recovery, and improving microcirculation through synergistic effects, thereby filling the gap in this treatment field.ObjectiveThis proposed trial aimed to evaluate the effectiveness and safety of UA (umbilical acupuncture) combined with WA (warm needle acupuncture) in treating residual numbness after LDH surgery. To verify the hypothesis that the combined method is superior to traditional electroacupuncture.MethodsThis proposed study is a single-center, single-blind, prospective, randomized controlled trial (RCT) involving patients with LDH who were hospitalized and underwent percutaneous endoscopic lumbar discectomy (PELD) at our hospital. Patients meeting the inclusion criteria will be randomly assigned to either the treatment group (umbilical acupuncture combined with warm needle acupuncture) or the control group (electroacupuncture). The participants will be assessed on the first day after surgery, and acupuncture treatment will begin on the second day and continue for three consecutive days, with each session lasting 30 minutes. After that, the treatment mixture was changed three times a week for four weeks. All patients received standard Western medical drug treatment. After the treatment is concluded, a six-month follow-up will be conducted. The primary efficacy indicator will be the visual analog scale (VAS) score for numbness. The secondary efficacy indicators will include the 10 g monofilament test, 40 g pressure acupuncture sensation examination, Japanese Orthopedic Association (JOA) score, lower limb electromyography (H-reflex differences, F-wave conduction velocity, and latency), VAS score, traditional Chinese medicine symptom scoring, and Short Form 36-Health Survey (SF-36) score. Any adverse events occurring during the trial will be recorded. The data will be analyzed according to a predefined statistical analysis plan.DiscussionThis trial combines UA with WA to create a new non-invasive treatment for numbness after LDH surgery, an area where current therapies are inadequate. If proven effective, this combination therapy could offer a safer and more effective alternative to drug treatment, and provide evidence for the integration acupuncture strategies.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/, identifier ITMCTR2024000328.